An automated approach to the alignment of compound refractive lenses. (18th May 2022) - Breckling, Sean; Kozioziemski, Bernard; Dresselhaus-Marais, Leora; Gonzalez, Arnulfo; Williams, Ajanaé; Simons, Hugh; Chow, Paul; Howard, Marylesa
Abstract : The efficacy of an automatic technique to align compound refractive lenses at beamline facilities is demonstrated. The algorithm is presented in its entirety, along with the results of numerical simulations and an implementation at the Advanced Photon Source at Argonne National Laboratory, USA. Abstract : Compound refractive lenses (CRLs) are established X‐ray focusing optics, and are used to focus the beam or image the sample in many beamlines at X‐ray facilities. While CRLs are quite established, the stack of single lens elements affords a very small numerical aperture because of the thick lens profile, making them far more difficult to align than classical optical lenses that obey the thin‐lens approximation. This means that the alignment must be very precise and is highly sensitive to changes to the incident beam, often requiring regular readjustments. Some groups circumvent the full realignment procedure by using engineering controls ( e.g. mounting optics) that sacrifice some of the beam's focusing precision, i.e. spot size, or resolution. While these choices minimize setup time, there are clear disadvantages. This work presents a new automated approach to align CRLs using a simple alignment apparatus that is easy to adapt and install at different types of X‐ray experiments or facilities. This approach builds on recent CRL modeling efforts, using an approach based on the Stochastic Nelder–Mead (SNM) simplex method. This method is outlined and its efficacy is demonstrated with numerical simulation that is tested in real experiments conducted at the Advanced Photon Source to confirm its performance with a synchrotron beam. This work provides an opportunity to automate key instrumentation at X‐ray facilities.